An immunohistochemical study of the diagnostic value of TREM-1 as marker for fatal sepsis cases. (3rd April 2019) - Maiese, A.; Bolino, G.; Mastracchio, A.; Frati, P.; Fineschi, V.
ABSTRACT: Triggering receptor expressed on myeloid cells-1 (TREM-1) is produced and up-regulated by exposure of myeloid cells to lipopolysaccharides or other components of either bacterial or fungal origin, which causes it to be strongly expressed on phagocytes that accumulate in inflamed areas. Because TREM-1 participates in septic shock and in amplifying the inflammatory response to bacterial and fungal infections, we believe it could be an immunohistochemical marker for postmortem diagnosis of sepsis. We tested the anti-TREM-1 antibody in 28 cases of death by septic shock and divided them into two groups. The diagnosis was made according to the criteria of the Surviving Sepsis Campaign. In all cases, blood cultures were positive. The first group was comprised subjects that presented high ante-mortem serum procalcitonin and the soluble form of TREM-1 (s-TREM-1) values. The second group comprised subjects in which s-TREM-1 was not measured ante-mortem. We used samples of brain, heart, lung, liver and kidney for each case to test the anti-TREM-1 antibody. A semiquantitative evaluation of the immunohistochemical findings was made. In lung samples, we found immunostaining in the cells of the monocyte line in 24 of 28 cases, which suggests that TREM-1 is produced principally by cells of the monocyte line. In liver tissue, we found low TREM-staining in the hepatocyte cytoplasm, duct epithelium, the portal-biliary space and blood vessel. In kidney tissue samples, we found the TREM-1 antibody immunostaining in glomeruli and renal tubules. We also found TREM-1 staining in the lumen of blood vessels. Immunohistochemical staining using the anti-TREM-1 antibody can be useful for postmortem diagnosis of sepsis.